Development of scores assessing the refluxogenic potential of diet of patients with laryngopharyngeal reflux - ENVER, NECATİ (SPRINGER, 2019)
Objective To develop clinical tools assessing the refluxogenic potential of foods and beverages (F&B) consumed by patients with laryngopharyngeal reflux (LPR). Methods European experts of the LPR Study group of the Young-Otolaryngologists of the International Federation of Oto-rhino-laryngological societies were invited to identify the components of Western European F&B that would be associated with the development of LPR. Based on the list generated by experts, four authors conducted a systematic review to identify the F&B involved in the development of esophageal sphincter and motility dysfunctions, both mechanisms involved in the development of gastroesophageal reflux disease and LPR. Regarding the F&B components and the characteristics identified as important in the development of reflux, experts developed three rational scores for the assessment of the refluxogenic potential of F&B, a dish, or the overall diet of the patient. Results Twenty-six European experts participated to the study and identified the following components of F&B as important in the development of LPR: pH; lipid, carbohydrate, protein composition; fiber composition of vegetables; alcohol degree; caffeine/theine composition; and high osmolality of beverage. A total of 72 relevant studies have contributed to identifying the Western European F&B that are highly susceptible to be involved in the development of reflux. The F&B characteristics were considered for developing a Refluxogenic Diet Score (REDS), allowing a categorization of F&B into five categories ranging from 1 (low refluxogenic F&B) to 5 (high refluxogenic F&B). From REDS, experts developed the Refluxogenic Score of a Dish (RESDI) and the Global Refluxogenic Diet Score (GRES), which allow the assessment of the refluxogenic potential of dish and the overall diet of the LPR patient, respectively. Conclusion REDS, RESDI and GRES are proposed as objective scores for assessing the refluxogenic potential of F&B composing a dish or the overall diet of LPR patients. Future studies are needed to study the correlation between these scores and the development of LPR according to impedance-pH study.
Keywords: Reflux; Diet; Laryngitis; Laryngopharyngeal; Score; Symptoms; Food; Beverage; LOWER ESOPHAGEAL SPHINCTER; UPPER GASTROINTESTINAL SYMPTOMS; PROTON PUMP INHIBITOR; LOW-ACID DIET; GASTROESOPHAGEAL-REFLUX; RISK-FACTORS; LIFE-STYLE; RED WINE; OTOLARYNGOLOGIC MANIFESTATIONS; ALCOHOL-CONSUMPTION